A light and electron microscopical study of the regenerating spinal cord of the Eel - Dervan, Adrian Gerard Niall (Trinity College (Dublin, Ireland). Department of Zoology, 2001)
The present study examined the regenerative capability o f the European eel Anguill anguilla following spinal cord transection injury using both light and electron microscopy. The primary aim of this investigation was to determine the role of the different cell types in the formation of a 'bridge' of regenerating tissue that facilitates the growth of axons back to their original targets. In addition, the chronological order for the appearance of the different cells was also investigated.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin